2011
DOI: 10.1007/s00125-011-2265-7
|View full text |Cite
|
Sign up to set email alerts
|

Homozygous carriers of the G allele of rs4664447 of the glucagon gene (GCG) are characterised by decreased fasting and stimulated levels of insulin, glucagon and glucagon-like peptide (GLP)-1

Abstract: Aims/hypothesis The glucagon gene (GCG) encodes several hormones important for energy metabolism: glucagon, oxyntomodulin and glucagon-like peptide (GLP)-1 and -2. Variants in GCG may associate with type 2 diabetes, obesity and/or related metabolic traits. Methods GCG was re-sequenced as a candidate gene in 865 European individuals. Twenty-nine variants were identified. Four variants that were considered to have a likelihood for altered functionality: rs4664447, rs7581952, Ile158Val and Trp169Ter, were genotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 26 publications
0
10
0
1
Order By: Relevance
“…Some of the mechanisms behind the lower GLP-1 response in both prediabetes and overweight may include genetic variation in the regulation of GLP-1 synthesis (3,31,32,39), since twin studies have shown that GLP-1 response has a heritability of up to 67% (31). Lower GLP-1 response has also been observed in the twin with diabetes of twin pairs discordant for type 2 diabetes (3).…”
Section: Potential Mechanismsmentioning
confidence: 99%
“…Some of the mechanisms behind the lower GLP-1 response in both prediabetes and overweight may include genetic variation in the regulation of GLP-1 synthesis (3,31,32,39), since twin studies have shown that GLP-1 response has a heritability of up to 67% (31). Lower GLP-1 response has also been observed in the twin with diabetes of twin pairs discordant for type 2 diabetes (3).…”
Section: Potential Mechanismsmentioning
confidence: 99%
“…Each patient was matched with respect to BMI, age, and sex with two randomly chosen control subjects from the Inter99 (11,12) or the Health (13) studies. A computer algorithm was applied to randomly select matching control subjects to be invited to participate in the study solely based on their best match with sex, BMI, and age.…”
Section: Study Participantsmentioning
confidence: 99%
“…In contrast, rs4664447 C/C (fwd strnd) of the GCG gene, which was -to our knowledge -the only previously reported risk genotype to be associated with a reduced GLP-1 response, occurs only in approximately 4 out of 10 000 individuals with European origin (Ensemble genomic database -Human -GRCh38.p13) [22,23]. Fig.…”
Section: Discussionmentioning
confidence: 89%